Higher Education Institutions’ appreciation and adoption of e-publishing in Macau, China - Yi Ye (Diversitas Journal, 2024)
The rapid digitization of scholarly communication has globally transformed the landscape of academic publishing. Through descriptive research, this study explored the appreciation and adoption of e-publishing strategies within higher education institutions in Macau, China. It aimed to establish a framework for effective e-publishing strategies in educational management to enhance teaching methodologies, student engagement, and learning outcomes. The research objectives included profiling higher education institutions based on enrolment figures, teaching modalities, institutional types, and learning facilities. Additionally, it assessed the level of appreciation of administrators, teachers, and students regarding electronically published learning materials in terms of quality, content, accessibility, and cost-effectiveness. Comparative analyses were conducted to discern differences in assessments among the three respondent groups. Furthermore, the study examined the relationship between institutional profiles and the level of appreciation for e-publishing. It also evaluated the extent of e-publishing adoption in academic management, administration, resource accessibility, and learning outcomes. There is a moderate adoption on the level of adoption of electronically published learning materials in terms of academic management, administration, and learning outcomes as assessed by the administrators, the teachers and the students. Ultimately, the findings yielded for the development of a strategic plan to promote the effective integration of e-publishing in higher education institutions in Macau, China.